If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -45x = 285 Solving 60 + -45x = 285 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -45x = 285 + -60 Combine like terms: 60 + -60 = 0 0 + -45x = 285 + -60 -45x = 285 + -60 Combine like terms: 285 + -60 = 225 -45x = 225 Divide each side by '-45'. x = -5 Simplifying x = -5
| k^2-16k+64=8 | | 3X+Y+24=0 | | -67+8x=59+x | | .5(-12+x)=3.5 | | x^4-4x^3-x^2+10x-24=0 | | X-9t=6 | | 7a-3=+6a | | p+4p-5=5 | | -3x-20=9-4x | | 7f+g=5-g | | 3X+Y-24=0 | | -2(5+6p)=-82 | | 21x=274 | | 6.75+1.25x=31.75 | | 10y+5-8y+10= | | b^2-16b+63=0 | | y-z=2 | | X^2+2=-3x+12 | | 5-2y-12=y+9 | | 0=3x^2+2x-4 | | 5(2x+3)=4(2-3x)+2(2+3x) | | 4(-6-5h)+2h= | | 9x-63=3x+93 | | 5(-2+3x)=-85 | | t-2s=5 | | 1/4a-4=4 | | 55.00+8.50x=123 | | 30+2+5n=70 | | -2x^2+30x-72=0 | | .05n+.10(n+9)+.25(n+30)=10.00 | | 5(y-2)+6=y+8 | | 13(4x)=52(13-x) |